18FDG PET/CT is sensitive but not specific for malignancy: two cases of disseminated tuberculosis mimicking metastatic cancer on imaging and clinical presentation - Maxime Collin; Bruno Krug; Marie-Cécile Nollevaux; Fanny Collette; Quentin Gilliaux; Laurence Faugeras; Lionel D'Hondt (European Journal of Case Reports in Internal Medicine)
Introduction: 18Fluorodeoxyglucose positron emission tomography/computed tomography (18FDG PET/CT) scan is widely used in the evaluation of suspected tumoral processes. In addition to its oncological applications, it is also employed in the diagnosis and follow-up of various conditions, including multiorgan tuberculosis. Case description: We report a case series of two young patients with exclusive extrapulmonary disseminated tuberculosis that mimicked a neoplastic process both clinically and on 18FDG PET/CT imaging. Initially, both patients were admitted to the oncology unit with a presumed diagnosis of cancer. However, following an exhaustive work-up, a definitive diagnosis of tuberculosis was established via histopathological and microbiological analysis. Conclusion: These cases underscore the importance of considering disseminated tuberculosis as a differential diagnosis during oncologic evaluations, especially in patients from endemic regions, and highlight the potential psychological impact of prematurely labelling a condition as cancer.